Impact of COVID-19-Related Lockdown on Psychosocial, Cognitive, and Functional Well-Being in Adults With Down Syndrome - Villani, Emanuele Rocco; Vetrano, Davide Liborio; Damiano, Cecilia; Paola, Antonella Di; Ulgiati, Aurora Maria; Martin, Lynn; Hirdes, John P.; Fratiglioni, Laura; Bernabei, Roberto; Onder, Graziano; Carfì, Angelo (Frontiers in Psychiatry, 2020)
People with Down Syndrome (DS) have a high prevalence of physical and psychiatric comorbidities and experience early-onset dementia. With the outbreak of CoVID-19 pandemic, strict social isolation measures have been necessary to prevent the spreading of the disease. Effects of this lockdown period on behaviour, mood and cognition in people with DS have not been assessed so far. In the present clinical study, we investigated the impact of CoVID-19-related lockdown on psychosocial, cognitive and functional wellbeing in a sample population of 46 adults with DS. The interRAI Intellectual Disability standardised assessment instrument, which includes measures of social withdrawal, functional impairment, aggressive behaviour and depressive symptoms, was used to perform a three time-point evaluation (two pre-lockdown and one post-lockdown) in 37 subjects of the study sample, and a two time point evaluation (one pre- and one post-lockdown) in 9 subjects. Two mixed linear regression models – one before and one after the lockdown – have been fitted for each scale in order to investigate the change in the time-dependent variation of the scores. In the pre-lockdown period, significant worsening over time (i.e., per year) was found for the Depression Rating Scale score (β=0.55; 95% CI 0.34; 0.76). In the post-lockdown period, a significant worsening in social withdrawal (β=3.05, 95% CI 0.39; 5.70), instrumental activities of daily living (β=1.13, 95% CI 0.08; 2.18) and depression rating (β=1.65, 95% CI 0.33; 2.97) scales scores was observed, as was a significant improvement in aggressive behaviour (β=-1.40, 95% CI -2.69; -0.10). Despite the undoubtful importance of the lockdown in order to reduce the spreading of the CoVID-19 pandemic, the related social isolation measures suggest an exacerbation of depressive symptoms and a worsening in functional status in a sample of adults with DS. At the opposite, aggressive behaviour was reduced after the lockdown period. This finding could be related to the increase of negative and depressive symptoms in the study population. Studies with longer follow-up period are needed to assess persistence of these effects.